Mausu’ah Hadis Pembiayaan Murabahah dalam Kitab Shahih Bukhari (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2018)
Buying and selling transactions using the credit system (installment) is one of the transactions commonly done by Indonesian people today, this transaction is very popular with the public, because buyers can directly use the product they dream of, without having to pay cash. This transaction certainly has been very popular in Indonesia, but there are still many of them who are still wondering, how is the law of the sale and purchase system according to Islamic law, whether the Prophet Muhammad ever did it. The results of the study found in Mausu’ah Bukhari there were two hadiths, the Book: Buying and selling,Chapter: The Prophet (PBUH) bought it by way of tempo, No. Hadith: 1926. Bukhari Hadith No. 1926 was supported by 15 traditions from several histories, namely: 7 hadith from the history of Bukhri, 3 hadiths from Muslim history, 2 hadiths from the narrations of Nasa’i, 1 hadith from the narrations of Ibn Maajah and 2 hadith from Ahmad nar. Book: evasive tactics, Chapter: Hibah and Syuf’ah, No. Hadith: 6462. Bukhari Hadith No. 6462 is supported by 12 traditions from several narrations, namely: 1 hadith from the history of bukhri, 1 hadith from the history of abu daud, 2 hadiths from the narrations of nasa’i, 2 hadiths from the history of Ibn Majah and 6 hadiths from Ria narrated Ahmad.